Co-digestão anaeróbia de glicerina bruta e efluente de fecularia - Larsen, Andrea Christina (2009)
The National Biodiesel Production and its Application Program, created by the Federal Government, introduces biodiesel in the Brazilian energetic matrix, bringing along the perspective to improve glycerin offer, a co-product of biodiesel production. Since for each 100 L of biodiesel, 10 kg of raw glycerin are produced, this implies on the development of studies for an economically viable use of glycerin. So, the main objective of this paper was to evaluate the addition of raw glycerin in anaerobic digestion of cassava starch production wastewater, in a semi-continuous-flux reactor of one-phase in bench scale. A 8.77 L reactor, with useful volume, was used, with PVC conduit as a support medium, temperature of 26±1º C, supplied with cassava starch production wastewater and glycerin, with hydraulic detention times of 4 and 5 d and organic loads of 3.05, 9.32, 14.83 e 13.59 g COD L-1 d-1, in this order, obtained with the addiction of glycerin at 0, 2, 3 and 2%, respectively. The biogas production per reactor volume increased with the 2% glycerin addiction with regard to the control treatment. However, in the next treatments, biogas production decreased when organic load increased. The major average biogas production per reactor volume was 1.979 L biogas L-1 d-1, for the organic load of 9.32 g COD L-1 d-1. The major averages of biogas production per g COD and g TVS consumed were 0.397 and 0.661 L, for the control treatment, without glycerin addition. The best COD removal, 98.69%, occurred for 2% glycerin treatment and 9.32 g COD L-1 d-1 organic load, followed by 96.41% for the control treatment. The major removal of TS and TVS occurred for the control treatment, for 2% glycerin treatment and organic load of 9.32 g COD L-1 d-1, by 81.19 and 75.47% TS and 90.21 and 81.18% TVS for the respective treatments. Thus, the evaluated reactor in this trial can be used for the treatment of cassava starch production wastewater with crude glycerin addition as a way of giving a correct destination to the last one, without using neutralizers and nutrients.